Method for producing porous monoliths by sol-gel process
The sol-gel method is used to form porous monomers in the container, which solves the problem of unadjustable size and shape in the prior art, and achieves efficient and uniform manufacturing of porous monomers, which is suitable for analytical chemistry and separation processes.
Patent Information
- Application Number
- JP2024538201
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-24
- Filing Date
- 2022-12-22
- Publication Date
- 2025-01-28
AI Technical Summary
The prior art is difficult to manufacture porous monomer materials with adjustable sizes and shapes, especially in diameters less than millimeters, and there are problems of structural inhomogeneity and low repeatability, affecting their efficiency in analytical chemistry and separation processes.
The sol-gel method is adopted to achieve the adjustable size and shape of the pores by forming the sol-gel prepolymer in the container, partially filling the container and controlling the pore structure during the gelation process, and then removing the mold to form the pore monomer, using water-soluble polymer and metal alkoxide as precursors to control the pore size and porosity.
The manufacturing of porous monomers in the range of 0.025mm to 5mm is achieved, with uniform pore structure and high repeatability, suitable for analytical chemistry and separation processes, and improves separation efficiency and material utilization.
Smart Images

Figure 2025502733000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing porous monoliths and to their uses. The present invention also relates in particular to the porous monoliths obtainable by said method, and to their uses. [Background technology]
[0002] Porous monoliths, especially hierarchically porous monoliths, exhibit unique mass transport properties, especially due to their multimodal interconnected porosity, which is related to the specific surface area that can be functionalized. The framework and pore size can be adjusted by varying the chemical composition and the parameters of the method used to prepare the material.
[0003] Monoliths are primarily manufactured in cylindrical form with a narrow range of pore size distribution and can be used for a variety of applications, such as separation, adsorption or detection of compounds of interest, or catalysis of chemical reactions.
[0004] The traditional method of producing porous monoliths, in particular that described in the paper Lu et al., JSST 95 (2020) MPH par decomposition spinodale [HPM by spinodal decomposition], consists in placing a solution in a mold during the separation of the solution into two bicontinuous phases by the sol-gel method, and at the exact moment of this separation, the solvent-rich phase separates from the other silica-rich phase to obtain a solidified gel, the solvent-rich phase forming the pores and the silica-rich phase forming the framework. The solution placed in the mold is then removed from the mold, obtaining a porous monolith after drying.
[0005] Much research and progress has been made in expanding the formulation composition and understanding the influence of the various components of the formulation on the structure of the porous monoliths produced by this method, thus improving the control of different levels of porosity and also diversifying the interface chemistry through the development of new formulations leading to new materials such as organic-inorganic hybrids or more recently carbon frameworks.
[0006] Each method described in the literature is adapted to the exact shape and size of a given monolith, and the structure of the monolith is highly dependent on the formulation, the preparation conditions and the shape of the mould used. It does not seem possible to control the structure independently of the size or aspect ratio of the final monolith. It is therefore necessary to adapt the formulation to the shape of the mould.
[0007] This technical problem of adapting specific formulations to monoliths of various sizes and aspect ratios indeed poses problems for seemingly simple shapes such as cylinders, in particular cylindrical monoliths with diameters between 0.2 mm and 2 mm, in terms of obtaining certain dimensions, as highlighted in the paper by Khoo et al., Talanta 224 (2021), Revue des materiaux pour colonnes chromato [Review of materials for chromatography columns]. This problem is explained in particular by the fact that the production of monoliths involves shrinkage due to the densification of the network and the concomitant expulsion of the solvent during the syneresis step, which generates edge non-uniformities of the monoliths, as described in the article Bruns, S., Muellner, T., Kollmann, M., Schachtner, J., Hoeltzel, A., & Tallarek, U. (2010), Confocal laser scanning microscopy method for quantitative characterization of silica monolith morphology, Analytical chemistry, 82(15), pp. 6569-6575. This problem of reducing the dimensions of the monoliths to sub-millimeter diameter values proves to be particularly limiting if it is desired to circulate small amounts of liquid within the monolith or to incorporate the monoliths into miniaturized devices.
[0008] In addition, current methods are poorly reproducible: even after industrialization, variability is observed in the manufacture of monoliths, especially with regard to expected retention times when used for chromatography.
[0009] It is therefore currently not possible to select a formulation that results in certain structural properties (skeleton size and porosity) and then obtain with sufficient reproducibility monoliths that are identical from a structural point of view but have different sizes, distributed over several orders of magnitude, whether of the same or different shapes.
[0010] If these technical obstacles related to the inherent variability and geometry of the implemented methods were overcome, it would pave the way for a much wider use of hierarchical porous monoliths, given their high potential and demonstrated efficiency in separation, adsorption and catalysis. More specifically, mastering freestanding monoliths with diameters of less than a millimeter would make it possible to support ongoing developments in analytical chemistry in terms of analytical throughput and volume reduction, for example for applications in the field of health. Finally, columns, extraction supports, catalysts and microsystems could all be manufactured by a single method, without the need to redeploy expertise or research to readjust experimental parameters, as required by a change in the format and / or size of the monolith.
[0011] In an attempt to reduce the volume of available free-standing monoliths, especially in the field of separations, the literature Miyazaki et al., J Chrom.A 1043 (2004) Disques MPH pour SPE [HPM disks for SPE] proposes to maintain the diameter at a few mm and reduce the thickness of the monolith in order to obtain monoliths in the shape of a disk. However, with this solution it is not possible to go below a thickness of 1 millimeter, since disks smaller than this value are fragile. In addition, the specific shape of the disk is not very suitable for the separation field, and the reduction of the monolith height leads to a reduction in the number of theoretical plates, which ultimately reduces the separation efficiency.
[0012] The paper Motokawa et al., J. Chrom A 961 (2002) Capillaires contenant un MPH [Capillaries containing an HPM] and the patent application EP 1 066 513 propose to form porous monoliths in situ in the capillary without removing them. This allows to have a large number of theoretical plates for separation, which is very useful for HPLC analysis. Such a method does not allow to produce free-standing monoliths with a diameter of micrometers, limiting the possibilities of integration and use. Moreover, only diameters between 0.025 and 0.2 mm are actually obtainable using this technique. Scanning electron microscope images show, on the one hand, that the mounting of the monoliths in the capillary is very often imperfect, opening up interstitial spaces that can be detrimental to the reproducibility and even the quality of the separation, and, on the other hand, that the structures are not similar even for the same formulation. In addition, to specifically limit edge effects in the capillary walls, significant changes must be made to the initial composition and process steps compared to larger free-standing monoliths, lengthening the preparation of such capillaries and introducing structural variability. Finally, the method has a low success rate in forming the desired monoliths in capillaries. [Prior art documents] [Patent documents]
[0013] [Patent Document 1] EP 1 066 513 [Non-patent literature]
[0014] [Non-Patent Document 1] Lu et al., JSST 95(2020)MPH par decomposition spinodale [HPM by spinodal decomposition] [Non-Patent Document 2] Khoo et al., Talanta 224 (2021), Revue des materiaux pour colonnes chromato [Review of materials for chromatography columns] [Non-Patent Document 3] Bruns, S., Muellner, T., Kollmann, M., Schachtner, J., Hoeltzel, A., & Tallarek, U. (2010), Confocal laser scanning microscopy method for quantitative characterization of silica monolith morphology, Analytical chemistry, 82(15), pp. 6569-6575. [Non-Patent Document 4] Miyazaki et al., J Chrom.A 1043 (2004) Disques MPH pour SPE [HPM disks for SPE] [Non-Patent Document 5] Motokawa et al., J. Chrom A 961 (2002) Capillaries contenant un MPH [Capillaries containing an HPM] Summary of the Invention [Problem to be solved by the invention]
[0015] There is therefore a need for a method for producing porous monoliths that are reproducible, can be sized to fit a wide range of sizes, particularly between at least 0.025 mm and 5 mm in diameter for cylindrical monoliths, and have a well-defined internal structure, particularly controlled pore size. [Means for solving the problem]
[0016] The present invention provides a method for producing a porous monolith, comprising the steps of: - forming a sol comprising a sol-gel precursor in an aqueous solution; - at least partially filling a preformed sol into a container and at least one mold contained in the container, the mold including at least one opening that opens into the sol after filling with the sol; - forming a sol-gel matrix from the sol in a container; - removing the mold with the sol-gel matrix contained therein from the mold container; - forming a porous monolith from the sol-gel matrix contained in the mold; This need is met by a method comprising:
[0017] The "sol-gel method" is a process for preparing a sol-gel compound having the formula M(OR) n , R'-M(OR) n-1 or a sodium silicate or titanium colloid as precursor, where M is a metal, transition metal or metalloid, in particular silicon, R or R' is an alkyl group and n is the oxidation degree of the metal. In the presence of water, hydrolysis of the alkoxy groups (OR) occurs, forming small particles, generally less than 1 nanometer in size. These particles aggregate to form clusters that do not precipitate but remain in suspension, forming a sol. The increase in the clusters and their condensation increases the viscosity of the medium and forms what is called a gel. The gel can then continue to evolve during a stage of aging, during which the polymer network present in the gel densifies. The gel then shrinks and, during a process known as syneresis, the solvent is expelled from the formed polymer network. The solvent then evaporates during a process called the drying process, resulting in a solid porous glass-type material, resulting in a porous monolith. The syneresis and drying steps may be simultaneous.
[0018] "Forming a sol-gel matrix in a container from a sol" means that a sol contained in a container including a mold is evolved by a sol-gel process to form a sol-gel matrix. The sol-gel matrix contained in the mold is materially continuous with the sol-gel matrix outside the mold, at least through the openings located below the level of the sol after filling, so as to form one block.
[0019] The presence of at least one opening in the mold below the level of the sol after filling allows the mold to be filled with the sol during the filling step and allows for fluidic circulation of the sol between the sol contained in the mold and the sol contained in the container during the remainder of the process.
[0020] By producing a large sol-gel matrix in a container and removing a portion of it contained in a mold during the formation of the matrix, it is possible to avoid the edge effects that occur in the above-mentioned methods by always producing the sol-gel matrix in a container of the same size.
[0021] Such a method allows the production of porous monoliths with similar textural properties over a wide range of diameters, regardless of whether the monoliths are free-standing or not, without reoptimizing or modifying the formulation of the initial mixture.
[0022] Such a method also allows for the simultaneous formation of multiple porous monoliths with identical textural properties by placing several moulds in a container.
[0023] It also makes it possible to obtain monoliths with a wide variety of shapes and aspect ratios, as well as diverse, reproducible and controlled internal structures.
[0024] Sol Preferably, the sol comprises a phase separation. Preferably, the sol comprises a pore former, which promotes the formation of pores, and in particular allows the formation of macropores in the sol-gel matrix.
[0025] The pore-forming agent may be selected from water-soluble polymers, in particular polyethylene glycol (PEG), poly(acrylic acid), sodium polystyrene sulfonate, poly(ethyleneimine) and mixtures thereof. The water-soluble polymer may have a molecular weight between 1,000 and 100,000 Daltons, preferably between 5,000 and 50,000 Daltons, and even better between 5,000 and 30,000 Daltons.
[0026] The concentration of the pore former, in particular PEG, may be between 0.015 and 0.35 g per mL of sol, preferably between 0.02 and 0.2 g per mL of sol. These values are based on the ratio which can be between 0.03 and 1 g of pore former, in particular PEG, per mL of sol-gel precursor, in particular tetramethoxysilane (TMOS), and preferably between 0.06 and 0.6 g of pore former, in particular PEG, per mL of sol-gel precursor, in particular tetramethoxysilane (TMOS).
[0027] The sol-gel precursor may be selected from alkoxides, in particular hydrolyzable and condensable organometallics, in particular zirconium alkoxides, in particular zirconium butoxide (TBOZ), zirconium propoxide (TPOZ), alkoxides of titanium, niobium, vanadium, yttrium, cerium, aluminum or silicon, in particular tetramethoxysilane (TMOS), tetraethoxysilane (TEOS), tetrapropoxysilane (TPOS), tetrabutoxysilane (TBOS), trimethoxysilanes, in particular methyltrimethoxysilane (MTMOS), propyltrimethoxysilane (PTMOS) and ethyltrimethoxysilane (ETMOS), triethoxysilanes, in particular methyltriethoxysilane (MTEOS), ethyltriethoxysilane (ETEOS), propyltriethoxysilane (PTEOS), aminopropyltriethoxysilane (APTES), sodium silicate, titanium colloids, and mixtures thereof.
[0028] The percentage of pore former in the sol and the percentage of sol-gel precursor in the sol are predetermined based on the properties of each sol-gel matrix, in particular the total porosity and average macropore size, from samples of known sol-gel matrices after gelation.
[0029] "Total porosity" means the ratio of the volume of the pores in the sol-gel matrix to the total volume of the sol-gel matrix. This value is between 0 and 1.
[0030] The method comprises: - preforming samples of sol-gel matrices containing various known proportions of a pore former and a sol-gel precursor of the monolith to be formed, - determining, after gelation, the characteristics of each sol-gel matrix of the samples, in particular the total porosity and the average macropore size; - selecting the properties of the formed porous monolith, in particular the total porosity and the average macropore size, in particular depending on the intended application; - determining the percentage of pore former in the sol and the percentage of sol-gel precursor in the sol as a function of the predetermined properties of the sample sol-gel matrix and the selected properties for the porous monolith to be formed; may include:
[0031] The method may include selecting a total porosity of the monolith to be formed and predetermining a ratio of a percentage of pore former to a percentage of sol-gel precursor in the sol as a function of the selected total porosity. The method may include selecting an average macropore size of the monolith to be formed and predetermining a percentage of pore former in the sol as a function of the selected average macropore size. The method may include selecting a total porosity and an average macropore size of the monolith to be formed and predetermining a percentage of pore former and a percentage of sol-gel precursor such that the ratio of the percentage of pore former in the sol to a percentage of sol-gel precursor corresponds to a total porosity selected on a predetermined curve of said ratio as a function of porosity and the percentage of pore former corresponds to an average macropore size selected on a predetermined curve of said ratio as a function of average macropore size.
[0032] The sol may contain additives, in particular acids, in particular acetic acid, or nitric acid, or succinic acid, and / or precursors of agents for dissolving the sol-gel matrix, in particular urea, or compounds with amide functional groups, in particular formamide, acetamide, N-methylformamide (NMF), and mixtures thereof.
[0033] The sol may contain between 0.001 mol / L and 2 mol / L of an acid, in particular acetic acid.
[0034] The sol may contain between 0.01 and 1.3 g / mL, preferably between 0.01 and 0.4 g / mL of a sol-gel matrix dissolving agent precursor, especially urea.
[0035] Preferably, the sol has a formulation that allows for phase separation by spinodal decomposition.
[0036] Alternatively, the sol is an emulsion or a template solution.
[0037] Sol formation The sol may be formed by stirring the sol-gel precursor, preferably the solution containing the sol-gel precursor and the pore former, for a period of time, in particular, of 5 minutes or more, better still of 10 minutes or more, even better still of 15 minutes or more. The stirring time may be less than 3 hours, better still of 2 hours or less. During the stirring, the temperature may be controlled at a substantially constant predetermined value, in particular between 0°C and 90°C, better still of 0°C and 50°C. This preliminary step of the sol preparation allows the sol-gel process to start before the phase separation, does not require any further mixing so that the sol solidifies with some phase separation, and ensures the homogeneity of the sol solution when transferred into a container.
[0038] filling The container can house several moulds, and the filling comprises filling the moulds with the sol, each mould comprising at least one opening that opens into the sol after filling. The moulds may be identical or not identical. The moulds may have different dimensions. This allows the production of several porous monoliths having the same internal structure and the same or different sizes or shapes at the same time. The filling of the container and moulds can be carried out by pouring the sol into the moulds contained in the container or by pouring the sol into the container containing the moulds, such that the openings are below the level of the sol after filling. The filling may be carried out by pouring the sol into the container, and the moulds are filled when the level of the sol in the container reaches the openings of the moulds. The filling may be carried out by pouring the sol into the moulds, and the container is filled when the level of the sol in the mould reaches the openings of the moulds.
[0039] Alternatively, the container and mould are filled by injecting the sol into the container and then at least partially, preferably gradually, immersing the mould in the sol contained in the container, and when the level of the sol reaches said opening, the or each mould is filled with sol through the opening.
[0040] Preferably, after filling, the mould is completely filled with the sol.
[0041] After filling, the mold may be completely immersed in the sol contained in the container.
[0042] Alternatively, the mold is partially immersed in the sol during filling.
[0043] The mould may have a single opening, in which case the, or each, opening of the mould is preferably oriented within the container towards the opening of the container through which the sol is injected, and the mould is preferably completely immersed in the sol after filling.
[0044] The mould may have at least two openings, at least one of which is below the level of the filled sol, and the other of the mould or each mould opening is within or outside the filled sol.
[0045] Preferably, the filling is carried out without the presence of air bubbles in the sol within the container and mould, and / or gradients in chemical composition and / or temperature.
[0046] Formation of the sol-gel matrix Formation of the sol-gel matrix may include condensation to form a gel, and optionally at least partial aging to densify the gel. The sol-gel matrix may be formed from the gel after condensation or from the gel after at least partial aging.
[0047] Preferably, forming the sol-gel matrix in the container does not include drying the sol-gel matrix.
[0048] During condensation the temperature may be kept substantially constant, in particular at a predetermined temperature between 15°C and 90°C, preferably between 25°C and 70°C.
[0049] The condensation may last for more than 10 minutes, better still for more than 20 minutes. The condensation may last for less than 4 hours, better still for less than 2 hours.
[0050] The at least partial maturation may last for at least 1 hour, better at least 3 hours, preferably at least 15 hours. The at least partial maturation may last for less than 2 weeks, in particular less than 72 hours. Preferably, the maturation period is short enough to limit the formation of mesopores and / or micropores.
[0051] The at least partial aging may be carried out at room temperature.
[0052] Preferably, the formation of the sol-gel matrix is carried out in the same manner in the container and in the mold. The overall porosity and pore size are preferably substantially uniform in the container and in the mold.
[0053] Sol-gel matrix Preferably, the sol-gel matrix obtained by forming the sol-gel matrix in the container has macropores, in particular macropores with dimensions of 50 nm or more. The macropores may have dimensions of 10 μm or less.
[0054] Preferably, the pores are interconnected in the sol-gel matrix.
[0055] Preferably, the concentration of the pore former is selected as a function of the macropore size selected for the porous monolith.
[0056] Preferably, the ratio between the concentration of the pore-forming agent and the concentration of the sol-gel precursor is selected as a function of the thickness of the scaffold of the sol-gel matrix selected for the porous monolith.
[0057] Removing the mold Removing the or each mold from the container together with the matrix it contains may include removing a block of sol-gel matrix containing the mold from the container, and removing the or each mold and the sol-gel matrix it contains from a previously removed block. Removing the or each mold from the block may be done by cutting the sol-gel matrix to the same height as the corresponding mold, or by breaking the sol-gel matrix surrounding the mold.
[0058] Alternatively, removal of the or each mold together with the matrix it contains can be performed by removing the corresponding mold from the sol-gel matrix surrounding it after removal of the block as described above, or directly in the container without prior removal of the block, particularly if the corresponding mold is only partially immersed in the sol-gel matrix.
[0059] Removal of matrix contained in mold Preferably, the sol-gel matrix contained in the or each mould is sufficiently coherent to enable it to be removed from the mould.
[0060] The method may include removing the or each mould contained sol-gel matrix from the corresponding mould.
[0061] Removal of the sol-gel matrix contained in the or each mould can be carried out by controlled pressure on said sol-gel matrix, for example by direct pressure by a solid of a size smaller than the mould, or by the pressure of a gas with a controlled flow rate.
[0062] Alternatively, the removal of the sol-gel matrix contained in the mould or moulds is carried out by opening the mould or moulds, in particular by cutting the mould or moulds, or by separating the two parts of the mould or moulds from each other. The mould may also be in the form of two parts which are mutually movable, in particular separable or movable relative to each other via a hinge.
[0063] The mould containing the sol-gel matrix may be immersed in a liquid during the step of removing the sol-gel matrix contained in the mould or moulds, which may facilitate removal of the sol-gel matrix.
[0064] Mesopore formation The method may include the controlled generation of mesoporosity in the sol-gel matrix so as to form a sol-gel matrix with hierarchical porosity. Preferably, this step is carried out after removing the or each mould from the container and before forming a porous monolith from the sol-gel matrix of the or each mould. In case of multiple moulds, this step may be carried out simultaneously on all the obtained sol-gel matrices or separately under substantially the same or different conditions of controlled generation of mesoporosity.
[0065] Preferably, the pore size obtained is less than 50 nm, better still between 2 and 50 nm.
[0066] This allows to obtain hierarchical porous monoliths, i.e., macropores with at least two orders of magnitude of pore size, preferably formed during the formation of the sol-gel matrix, and mesopores formed during the controlled generation of mesopores. Such porous monoliths have a large internal surface area, increasing the exchange surface area between the passing liquid and the material, minimizing the distance covered by diffusion. In addition, this reduces the risk of breakage while giving flexibility to the sol-gel matrix. It also reduces the drying time of the sol-gel matrix.
[0067] The controlled generation of mesoporosity can be carried out in the sol-gel matrix while it is still in the mold, the sol-gel matrix with hierarchical porosity may or may not be removed from the mold, or the controlled generation of mesoporosity can be carried out after the sol-gel matrix is removed from the mold.
[0068] The controlled creation of mesoporosity is achieved by immersing the sol-gel matrix, whether or not removed from the mold or molds, in an aqueous mesoporosity creating solution that contains an agent that dissolves the sol-gel matrix and / or a precursor of an agent that dissolves the sol-gel matrix.
[0069] The lysis agent can be, for example, ammonium hydroxide, sodium hydroxide, or hydrofluoric acid at a concentration of 1M, or a mixture thereof.
[0070] The sol-gel matrix dissolving agent precursor can be a compound having urea or amide functional groups, especially formamide, acetamide, N-methylformamide (NMF) and mixtures thereof.
[0071] The amount of sol-gel matrix dissolving agent precursor is between 0.01 and 1.3 g per mL of initial sol, preferably between 0.01 and 0.4 g per mL of initial sol.
[0072] The solution for generating mesoporosity may include the sol-gel matrix dissolving agent precursor described above and a dissolving agent described above.
[0073] Preferably, when the solution for generating mesoporosity comprises a sol-gel matrix dissolving agent precursor, the solution for generating mesoporosity is heated to a temperature above room temperature.
[0074] Preferably, the concentration of the solubilizing agent and / or solubilizing agent precursor is such as to allow a localized dissolution of the sol-gel matrix in such a way as to form mesopores in the sol-gel matrix without dissolving it as a whole. The ratio between the volume of the solubilizing agent and / or solubilizing agent precursor and the volume of the sol-gel matrix can be selected as a function of the duration of the process of controlled generation of mesoporosity, the temperature at which this process is carried out, and the concentration of the solubilizing agent.
[0075] By such methods, mesopores of perfectly controlled size can be obtained.
[0076] Preferably, the controlled generation of mesoporosity lasts less than 50 hours, better less than 20 hours. The controlled generation of mesoporosity can last more than 0.5 hours, better more than 10 hours, even better more than 20 hours. During this step, the temperature of the sol-gel matrix can be 30° C. or more, better more than 60° C. and / or 150° C. or less, better less than 120° C. The temperature can be kept substantially constant during this treatment. This step can be carried out in an autoclave.
[0077] Alternatively, the method does not involve the creation of mesoporosity.
[0078] Formation of the Monolith In case of multiple moulds, the formation of the monoliths can be carried out simultaneously for all the obtained sol-gel matrices.
[0079] Formation of the porous monolith may involve at least partial maturation to densify the sol-gel matrix, especially if maturation has not been performed completely beforehand.
[0080] Formation of the porous monolith may include drying the sol-gel matrix, whether or not removed from the mold or molds, to form a dried sol-gel matrix. The drying step may be carried out under a flow of air or an inert gas, particularly dinitrogen, argon or carbon dioxide, helium, or dioxygen or dihydrogen.
[0081] Drying is preferably carried out thereafter if controlled generation of mesoporosity is to be carried out.
[0082] The drying step may be at least 5 hours and / or less than 20 hours.
[0083] The drying step can be carried out under critical conditions, better still under supercritical conditions, in particular in an autoclave or a freeze-drying apparatus.
[0084] The formation of the porous monolith may include a heat treatment of the sol-gel matrix, whether or not removed from the mold or molds, in particular after drying. The heat treatment may be carried out by gradual heating in a closed container under a flow of air or an inert gas, in particular dinitrogen, argon or carbon dioxide, helium, or dioxygen or dihydrogen, followed by maintaining the final temperature for a given time. The gradual heating may consist of an increment of 0.5°C / min until a temperature of 300°C or more is reached, better still 340°C or more, for example substantially 350°C, so as to obtain a porous monolith. The final temperature may be maintained for more than one hour. This allows the structure of the monolith to be stabilized and the organic residues resulting from the synthesis to be removed.
[0085] If the sol-gel matrix is to be removed from the mould or moulds, this is advantageously done prior to the formation of the porous monolith.
[0086] container The vessel may include a system for controlling the temperature within the vessel.
[0087] Preferably, the container is configured to accommodate a plurality of moulds.
[0088] The container may be cylindrical or conical, in particular with a polygonal, elliptical, oval or circular base.
[0089] The container may be made of plastic, in particular polytetrafluoroethylene (PTFE), polypropylene (PP), polyethylene (PE), polycarbonate (PC), polyethylene terephthalate (PET), polyvinyl chloride (PVC), or glass or stainless steel.
[0090] The volume of the container can be 0.5 mL or more.
[0091] Type Preferably, the mould is completely contained within the container, or alternatively, the mould may extend beyond the container.
[0092] The mould may have a single opening. The mould is then preferably completely contained in the container, and the filling of the sol is preferably carried out by filling the mould, and the filling of the container is carried out when the level of the sol reaches the mould or at least one mould opening. In this case, the mould is preferably completely immersed in the sol after filling.
[0093] The mould may have at least two openings. The mould may then be filled with the sol by filling the container with the sol, the mould may be fully or partially immersed in the sol as long as at least one of the openings of the or each mould is open into the sol after filling.
[0094] Preferably, the mould is placed in the container such that one of the openings is located at the bottom surface of the mould within the container.
[0095] The mould may be made of plastic, in particular polytetrafluoroethylene (PTFE), polyetheretherketone (PEEK), polyethylene (PE), polypropylene (PP) or polylactic acid, or of glass, in particular fused silica or borosilicate, or of stainless steel. The mould may be formed by 3D printing or casting.
[0096] The mold may be made of a porous body.
[0097] The mould, or at least one of the moulds, and better yet each mould, may be a hollow cylinder, in particular a rotating cylinder.
[0098] The, or at least one, mould, or better each mould, may be open at two opposite ends thereof. The, or each mould, may be disposed within the vessel with its longitudinal axis extending vertically within the vessel.
[0099] The, or at least one, mould, and better each mould, may have a cavity having a maximum lateral dimension, particularly a diameter, of 100 mm or less, better still 20 mm or less, even better still 13 mm or less, better still 8 mm or less, and / or 0.025 mm or more.
[0100] The volume of the, or each, mould may be greater than or equal to 10 nL and / or less than or equal to 400 mL, better still between 30 nL and 100 mL. The, or at least one, mould, better still each mould, may have a height that exceeds its greatest lateral dimension, in particular its diameter.
[0101] The mould, or at least one of the moulds, and better yet each mould, may have two openings extending into opposing walls.
[0102] The or at least one mould, and better each mould, may be hollow and spherical, cylindrical or conical, in particular cylindrical or conical with a polygonal, elliptical, oval or circular base. The mould may have at least one open end, and better two opposite open ends, and in particular form an opening in the form of an open tube at its two ends.
[0103] The opening may have a circular contour.
[0104] The method can exclude the step of removing the sol-gel matrix from the or each mold, which forms a casing for the porous monolith, in which case the mold is a capillary, or made of a heat shrinkable material, or may be a pipette tip.
[0105] Capillary The mould may be a capillary having an internal diameter between 5 μm and 3 mm, better still between 25 μm and 500 μm.
[0106] The capillary may be made of fused silica. The capillary may have an interior surface that has been activated through a previous activation step.
[0107] In this case, the method can exclude the step of removing the sol-gel matrix from the capillary.
[0108] In the case where the porous monolith is within a capillary in which it is formed, the manufacturing method excludes the step of shrinking, especially heat shrinking, the mould, especially the capillary, on the porous monolith.
[0109] In this case, the creation of mesoporosity is preferably carried out by heating the capillary, if applicable, in an aqueous solution comprising a dissolution agent precursor, in particular urea, as described above.
[0110] Monolith Preferably, the sol-gel matrix is removed from the or each mould and the resulting porous monolith is self-supporting.
[0111] Preferably, the porous monolith is a hierarchical porous monolith.
[0112] The porous monolith may have a diameter less than or equal to 10 mm, better still less than or equal to 6 mm and / or greater than or equal to 0.02 mm.
[0113] Preferably, the porous monolith is free-standing and has a diameter of 1 mm or less, or the porous monolith is within a capillary and has a diameter of 0.2 mm or more.
[0114] The porous monolith may contain macropores, ie pores with dimensions greater than or equal to 50 nm, and mesopores, ie pores with dimensions between 2 and 50 nm.
[0115] The porous monolith may have a substantially uniform structure throughout its volume.
[0116] The porous monolith may have an aspect ratio, defined as its height to its largest lateral dimension, of 0.2 or more, better 0.4 or more, better 1 or more, and / or 1,000 or less, better 500 or less, even better 100 or less, better 50 or less, and even better 20 or less.
[0117] Preferably, the porous monolith is cylindrical, in particular cylindrical of revolution, with a polygonal, elliptical or circular base.
[0118] The monolith can be free-standing and the method may include inserting the free-standing porous monolith into a heat shrink tube, a pipette tip or a solid phase extraction cartridge, and, in the case of heat shrink tube, heating the heat shrink tube to encapsulate the porous monolith within the tube.
[0119] The method may include modification of the porous monolith after manufacture, in particular functionalization of the surface of the porous monolith. The surface of the porous monolith may be covered with molecules such as hydrophobic hydrocarbon ligands (e.g., octadecyl ligands) or hydrophilic ligands such as 2,3-dihydroxypropyl derivatives. The ligands of such modified columns can be further modified using known procedures. Porous catalyst or enzyme supports can be prepared by adding enzymes, such as glucose isomerase, or catalytic metal elements, such as platinum and palladium.
[0120] The invention also relates to free-standing porous monoliths, especially obtainable using the method described above, having a maximum lateral dimension strictly less than 1 mm.
[0121] The free-standing porous monolith may have a maximum lateral dimension of 20 μm or greater.
[0122] Preferably, the porous monolith is a hierarchical porous monolith.
[0123] The porous monolith may contain macropores, ie pores with dimensions greater than or equal to 50 nm, and mesopores, ie pores with dimensions between 2 and 50 nm.
[0124] The porous monolith may have substantially uniform porosity throughout its volume.
[0125] The porous monolith may have an aspect ratio of 0.2 or more, better 0.4 or more, and / or 1,000 or less, better 100 or less, even better 50 or less, preferably 20 or less.
[0126] Preferably, the porous monolith is cylindrical with a polygonal, elliptical or circular base, in particular a cylinder of revolution.
[0127] The invention also relates to the assembly of a mould, in particular a capillary, with a porous monolith contained in the mould, in particular obtained using the method described above, and including a maximum lateral dimension strictly greater than 200 μm.
[0128] Preferably, the porous monolith is produced in a mould by filling at least one cross section of the mould and without the step of shrinking, in particular heat shrinking, the mould onto the porous monolith.
[0129] When the porous monolith is within the mold in which it was formed, the porous monolith may have a cross-section substantially equal to the internal cross-section of the mold, particularly the capillary, over its entire length, including the portion without the porous monolith.
[0130] Preferably, the porous monolith is a hierarchical porous monolith.
[0131] The porous monolith may contain macropores, ie pores with dimensions greater than or equal to 50 nm, and mesopores, ie pores with dimensions between 2 and 50 nm.
[0132] The porous monolith may have substantially uniform porosity throughout its volume.
[0133] Preferably, the assembly is characterized in that it has no continuous fluid path between the wall of the capillary and the porous monolith connecting portion of the capillary that extends for a length at least 20 times longer than the average macropore diameter, and better still for a length at least 10 times longer than the average macropore diameter.
[0134] Preferably, the mould, in particular the capillary, does not undergo deformation, in particular deformation due to heating during the formation of the assembly. Preferably, the mould, in particular the capillary, does not exert compressive forces on the porous monolith, in particular as a result of the shrinking process during the formation of the assembly.
[0135] If the porous monolith is within the capillary in which it is formed, the manufacturing method excludes a step of shrinking, in particular a step of heat shrinking, of a mould, in particular the capillary, on the porous monolith.
[0136] The porous monolith may have an aspect ratio of 0.2 or more, better 0.4 or more, and / or 1,000 or less, better 100 or less, even better 50 or less, preferably 20 or less.
[0137] Preferably, the porous monolith is cylindrical, in particular a cylinder of revolution.
[0138] use The present invention also relates to a method for liquid phase chromatography, separation and / or extraction and / or adsorption of compounds of interest in complex liquid mixtures, filtration of liquids or catalysis of liquids by passing a liquid through a porous monolith obtainable by the above described method or through the above described porous monolith.
[0139] The method may include incorporating the free-standing monolith into a heat shrink tubing and incorporating the tubing into a fluid flow system. [Brief description of the drawings]
[0140] [Figure 1] FIG. 1 shows a schematic representation of the various steps of a method for producing a porous monolith according to the invention. [Diagram 2] FIG. 1 shows an example of a free-standing porous monolith produced by a method according to the present invention. [Diagram 3] FIG. 1 shows images obtained by scanning electron microscopy for monoliths of different diameters. [Figure 4]FIG. 2 is a graph showing pore volume versus pore diameter for a porous monolith. [Diagram 5] 1A-1D show the steps of separation of a mixture of dyes in a porous monolith obtained by the method according to the invention. [Figure 6] FIG. 1 is a ternary diagram showing the molar ratio of PEG as a function of the molar ratio of the solvent (including water, the formed alcohol and the catalyst) and the molar ratio of the gel (SiO2) formed in the sol-gel matrix at the end of gelation. [Figure 7] FIG. 2 is a cross-sectional view of an 800 μm diameter monolith formed by the method of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0141] FIG. 1 shows the various steps of the method for producing a porous monolith.
[0142] The method comprises a first step, not shown, of forming an aqueous solution of the pore-forming agent and the sol-gel precursor and possible additives, in particular an acid and / or a matrix dissolving agent.
[0143] The pore-forming agent may be selected from water-soluble polymers, in particular polyethylene glycol (PEG), poly(acrylic acid), sodium polystyrene sulfonate, poly(ethyleneimine).
[0144] The water-soluble polymer may have a molecular weight between 1,000 and 100,000 daltons, preferably between 5,000 and 50,000 daltons, and even better between 5,000 and 30,000 daltons.
[0145] The concentration of the pore former, in particular PEG, can be between 0.015 g and 0.35 g per mL of sol, preferably between 0.02 and 0.2 g per mL of sol. These values are linked to the concentration of the sol-gel precursor, in particular tetramethoxysilane (TMOS), and are based on values of 0.03 to 1 g of pore former, in particular PEG, per mL of sol-gel precursor, in particular tetramethoxysilane (TMOS), and preferably on values of 0.06 to 0.6 g of pore former, in particular PEG, per mL of sol-gel precursor, in particular tetramethoxysilane (TMOS). It is selected according to the macropore size desired in the final porous monolith.
[0146] The sol-gel precursor may be selected from alkoxides, in particular hydrolyzable and condensable organometallic compounds, in particular zirconium alkoxides, in particular zirconium butoxide (TBOZ), zirconium propoxide (TPOZ), alkoxides of titanium, niobium, vanadium, yttrium, cerium, aluminum or silicon, in particular tetramethoxysilane (TMOS), tetraethoxysilane (TEOS), tetrapropoxysilane (TPOS), tetrabutoxysilane (TBOS), trimethoxysilanes, in particular methyltrimethoxysilane (MTMOS), propyltrimethoxysilane (PTMOS) and ethyltrimethoxysilane (ETMOS), triethoxysilanes, in particular methyltriethoxysilane (MTEOS), ethyltriethoxysilane (ETEOS), propyltriethoxysilane (PTEOS), aminopropyltriethoxysilane (APTES) and mixtures thereof, such as TMOS. It is also possible to use precursors such as sodium silicate or titanium colloids, especially if the purity requirements allow, ie are not too high.
[0147] The percentage of pore former in the sol and the percentage of sol-gel precursor in the sol are predetermined based on the properties of a sample of known sol-gel matrix taken immediately after gelation, in particular the total porosity and the average macropore size. This is particularly shown in FIG. 6, a ternary diagram with the percentage of pore former (in this case PEG), the percentage of gel in the matrix (the percentage of SiO2 formed by gelation of TMOS) and the percentage of solvent (including water, generated alcohol and catalyst) as data. The sum of these three data is always 100%. Sol-gel matrices A to H with different percentages of the aforementioned data were cast. The total porosity and the average macropore size formed in each sol-gel matrix were determined. Sol-gel matrices A to F all have the same percentage of gel in the matrix (SiO2) but different percentages of pore former, which decrease in particular from A to E. It can be seen that the total porosity remains essentially constant and the average pore size increases from A to E. Sol-gel matrices G, C and H have substantially the same amount of solvent but different ratios of the amount of pore former to the amount of gel (SiO2) in the sol-gel matrix, specifically decreasing from G to C to H. It can be seen that the pore size remains substantially constant while the total porosity decreases from G to C to H. Thus, for a pore former / sol-gel precursor pair, it is easy to determine the ratio of pore former and sol-gel precursor that allows the formation of a porous monolith with a particular total porosity and average macropore size.
[0148] The solution is then stirred for a period of time between 5 minutes and 3 hours, and even better between 15 minutes and 2 hours, at a controlled and substantially constant temperature between 0° C. and 90° C., and better between 0° C. and 50° C. This stirring step allows the sol-gel process to begin before phase separation to form sol 5.
[0149] Then, in step 20, sol 5 is added to the container 12 so as to at least partially fill said container 12 and at least one mold 15 contained therein.
[0150] The mold 15 can be placed in a container that is gradually filled with the sol 5 so that the mold 15 is gradually filled without the presence of air bubbles or chemical composition gradients. Filling can be carried out until the mold 15 is completely immersed. Partial immersion is also possible. It is also possible to add the mold to the sol 5 contained in the container 12.
[0151] The container 12 may be configured to accommodate multiple identical or different molds 15. The container 12 may be cylindrical as shown, or may have other shapes. The container 12 may be made of plastic, particularly PTFE, PP, PE, PC, PET, PVC, or glass or stainless steel.
[0152] The mould 15 has two openings 17 and 18 on opposite surfaces of the mould 15, at least one of the two openings, 17, being below the level of the sol after filling. Such openings allow the mould 15 to be filled by filling the container 12 housing the mould 15, or by at least partially immersing the mould 15 in the sol 5 contained in the container 12 and circulating the sol 5 between the interior and exterior of the mould before the entire sol condenses. In the illustrated example, the mould 15 is in the form of a tube open at both ends and extending vertically within the container 12, but it can be quite different, the tube can have a different orientation within the container and / or the mould can have another shape.
[0153] The mold 15 may be completely contained within the container 12 as shown, or may extend beyond the container 12. In the former case, the mold 15 may or may not be completely immersed in the sol 5 after filling.
[0154] The mould 15 may be made of plastic, in particular PTFE, PEEK, PE, PP, or polylactic acid, or glass or stainless steel, in particular fused silica or borosilicate.
[0155] The mold may be made of a porous body.
[0156] The mold may be formed by 3D printing or casting.
[0157] The maximum lateral dimension of the cavity of the mould 15, in particular the diameter d of this cavity, may be between 13 mm and 0.025 mm.
[0158] Once the sol 5 is placed in the container 12 and mold 15, condensation occurs throughout the container and mold in step 30. This sol-gel transition may be followed by at least partial maturation (or aging) throughout, which ensures the formation of uniform macropores of similar properties in the formed sol-gel matrix 22, regardless of their shape and size.
[0159] During the condensation, the temperature can be kept substantially constant, in particular between 15° C. and 90° C., preferably between 25° C. and 70° C., for a period between 10 minutes and 4 hours. The duration of the condensation and the predetermined temperature depend on the desired internal structure of the sol-gel matrix and the stirring time of the initial solution in the sol formation step.
[0160] The at least partial ageing may last between 30 minutes and 2 weeks, in particular less than 72 hours, at room temperature. Preferably, the ageing period is short enough to prevent the formation of mesopores and / or micropores.
[0161] The block of sol-gel matrix 22 containing the mold 15 is then removed from the container 12 in step 40. If the mold 15 is only partially immersed, as will be seen below, this step may be optional.
[0162] The mold 15 together with the sol-gel matrix 25 it contains is then removed from the porous solid in step 50, for example by cutting the sol-gel matrix of the block 22 flush with the mold and then removing the mold 15 together with the sol-gel matrix it contains, or by breaking the sol-gel matrix of the block 22 around the mold 15. If the immersion was partial, the mold 15 together with the sol-gel matrix 25 it contains can be removed from the previously removed block or directly from the container 12.
[0163] The sol-gel matrix 25 can then be removed from the mold 15 in step 50. This is achieved by controlled pressure applied to the sol-gel matrix 25 while holding the mold 15. The pressure can be obtained by a plastic or glass solid, such as a fused silica capillary, or any other fairly strong material smaller in size than the mold 15, or by a gas with a controlled flow rate. The removal operation can be facilitated by immersing the assembly of the mold 15 and the sol-gel matrix 25 in a liquid. It is optionally possible to generate a slight pressure difference by gently tapping the assembly of the mold 15 and the sol-gel matrix 25 to remove the sol-gel matrix 25. Alternatively, the sol-gel matrix 25 is held in the mold 15, especially if the maximum lateral dimension of the mold is small, especially between 0.02 mm and 0.3 mm.
[0164] Once the mould 15, together with the sol-gel matrix 25 it contains, has been removed from the block 22 or container, or once the sol-gel matrix 25 has been removed from the mould 15, the method may include a step of controlled generation of mesoporosity. This step may be carried out by immersing the sol-gel matrix 25 or the mould / sol-gel matrix assembly in a basic solution, for example a 1M ammonium hydroxide solution, or by heating the material in water in the presence of a precursor, for example urea, generating ammonia in situ. It should be noted that in a second method, the ammonium hydroxide can be added. This operation may last for between 0.5 and 50 hours, at a predefined, substantially constant temperature of the sol-gel matrix, between 30° C. and 150° C. This step may be carried out simultaneously, i.e. in the same bath, for several sol-gel matrices, whether they are from the same block or not.
[0165] Preferably, the pore size obtained is less than 50 nm, better still between 2 and 50 nm.
[0166] The sol-gel matrices obtained, or the moulds together with the sol-gel matrices they contain, are then dried. For this purpose, they are placed in a closed vessel, in particular an autoclave, and dried under critical or supercritical conditions, in particular under a flow of air or an inert gas, in particular dinitrogen (N2), for a period of 10 to 20 hours. They are then subjected to a gradient of 0.5°C / min under a flow of inert gas (other gases may also be used) until 350°C is reached, with a plateau at this last temperature for several hours. These steps can be carried out simultaneously for several sol-gel matrices, i.e. in the same closed vessel, whether they are from the same block or not.
[0167] Ready-to-use monoliths are thus obtained. Examples of monoliths with different diameters and heights are shown in Figure 2. These monoliths are all produced simultaneously from a sol using molds of different sizes, as described in the examples below.
[0168] The resulting porous monolith may contain macropores, ie pores with a selected dimension greater than or equal to 50 nm, and mesopores, pores with a selected dimension between 2 and 50 nm.
[0169] The porous monolith may have a substantially uniform structure throughout its volume, as can be seen in FIG.
[0170] The macroporosity of different monolith diameters obtained with different moulds of different sizes in the same container, observed by scanning electron microscopy (SEM), is shown in Figure 3. Image a) corresponds to a porous monolith with a diameter of 5 mm, image b) corresponds to a porous monolith with a diameter of 0.8 mm and image c) corresponds to a porous monolith with a diameter of 0.3 mm.
[0171] Figure 4 shows the distribution of pore diameters p in nanometers as a function of pore volume V for a porous monolith according to the following example with a step for controlling the production of mesoporosity. From this graph it can be seen that the distribution of pore diameters p has mainly two pore diameters p, around 20 nm, corresponding to mesopores, and around 2 μm, corresponding to macropores. This graph shows that the method allows precise control of the pore diameters of the porous monolith.
[0172] The porous monolith may have an aspect ratio, defined as the height to the largest lateral dimension, of between 0.2 and 100.
[0173] The monolith may be free-standing and the method may include inserting the or each free-standing porous monolith into a heat shrink tube or a pipette tip, and, in the case of heat shrink tube, heating the heat shrink tube to encapsulate the porous monolith within said tube.
[0174] The method may also include post-production modification of the porous monolith, in particular functionalization of the internal surface of the porous monolith. Functionalization may be carried out using organosilanes, in particular chlorosilanes (e.g., octadecyltrichlorosilane) and alkoxysilanes (octadecyltriethoxysilane, aminopropyltriethoxysilane, propyltrimethoxysilane), or hexadimethylsilazane, using liquid or gas phase processes.
[0175] The resulting porous monolith can then be incorporated into a fluid flow system using, for example, heat shrinkable tubing, for example made of polytetrafluoroethylene (PTFE).
[0176] Alternatively, the mould may be a fused silica capillary having an inner diameter of 5 μm to 3 mm, better still 5 μm to 500 μm. In this case, the method may exclude the step of removing the sol-gel matrix from the capillary. The capillary may have an activated inner surface through a previous activation step.
[0177] In this case, the creation of mesoporosity and / or microporosity is preferably carried out by heating the capillary in water containing a precursor, in particular urea as mentioned above.
[0178] Alternatively, the mould may have only one opening, the latter opening into the sol after filling, allowing circulation of the sol between the mould and the container.
[0179] Alternatively, the initial solution may be an emulsion or template solution containing the sol-gel precursors.
[0180] Working Example The synthesis of a free-standing monolith with a diameter of about 800 μm, with macropores of about 2 μm and mesopores of about 15 nm, produced by immersion in a basic solution, is described in detail below. In this example, several monoliths (at least about 10) are produced simultaneously by placing several molds in a container.
[0181] A solution is prepared by mixing 0.33 g of PEG with 2 mL of TMOS in 4 mL of 0.01 M acetic acid. The solution is stirred at 0° C. for 30 min to form a sol, which is then transferred to a polypropylene (PP) container with a PTFE tube of approximately 1 mm diameter previously placed vertically. The filling is performed by gradually adding the sol into the container from the bottom using a micropipette. The amount of solution added is such that the mold is completely immersed.
[0182] The container is placed at a temperature of 40° C. and gelation occurs between 45 and 50 minutes after transfer to the container. After gelation has taken place, the gel is left to mature at 40° C. for 24 hours. The sol-gel matrix resulting from gelation and maturation is then removed from the container and broken with metal pliers to recover the mold embedded within it. The monolithic sol-gel matrix enclosed in the mold is then removed with the aid of manual pressure exerted by a tube with a diameter of less than 1 mm. In this procedure, this pressure from the solid tube is sufficient to remove the monolith and does not weaken the gel.
[0183] The sol-gel matrix obtained is quickly immersed in a 1M NH4OH solution, adhering to a ratio of approximately 5 between the volume of the basic solution and the volume absorbed by the sol-gel matrix.
[0184] The matrix obtained is then placed in an autoclave, which is placed in an oven and connected by a tube allowing the circulation of gas. The gel is then dried under N2 for 12 hours. Finally, a heat treatment is carried out with a ramp of 0.5°C / min up to 350°C and a plateau at this last temperature for 2 hours.
[0185] The obtained monoliths are used, for example, in the field of liquid phase chromatography to overcome certain limitations inherent to solid phases consisting of particles compressed between two frits or for the separation / extraction of compounds of interest present in complex mixtures. The advantages of these materials have also been demonstrated in the field of catalysis.
[0186] FIG. 5 illustrates the use of one of the prefabricated porous monoliths 35 to separate two dyes from a mixture 65 of two dyes.
[0187] In photo a), the porous monolith 35 is introduced into a heat-shrinkable tube 68 that is heated. The assembly of the heat-shrinkable tube 68 incorporating the porous monolith 35 is incorporated into a fluid flow system, and in photo b), a mixture of two dyes 65 is introduced into the heat-shrinkable tube 68 at one end of the porous monolith by the fluid flow system. The mixture is loaded into the porous monolith 35. When the mixture is loaded into the porous monolith, separation of the two dyes, namely the yellow dye 66 at the head and the blue dye 67 at the tail, is observed, as shown in photo c). At the outlet of the porous monolith, after drying and elution, first the yellow dye 66 emerges, as shown in photo d), and then the blue dye 67, as shown in photo e). The two dyes 66 and 67 are well separated at the outlet.
[0188] The invention is not limited to the examples just described. The mold may be different as long as it can be filled with sol and can be in fluid communication with the sol contained in the container. [Explanation of symbols]
[0189] 5. Zoll 12 containers 15-inch 17 Opening 18 Openings 22 Sol-gel matrix blocks 25 Sol-gel matrix 10 steps 20 steps 30 steps 40 processes 50 steps 60 processes d diameter of cavity h Cavity height p pore diameter 35 Porous Monolith 65 Mixture of two dyes 66 yellow dye 67 Blue dye 68 Heat shrink tubing
Claims
1. A method for producing a porous monolith (35), comprising the steps of: - forming a sol (5) comprising a sol-gel precursor in an aqueous solution; - at least partially filling a container (12) and at least one mould (15) contained in the container (12) with a preformed sol (5), the mould (15) comprising at least one opening (17) which opens into the sol (5) after filling with the sol; - forming a sol-gel matrix (22, 25) from the sol (5) in a container (12); - removing the mould (15) together with the sol-gel matrix (25) contained therein from the container; - forming a porous monolith (35) from a sol-gel matrix (25) contained in a mould (15); wherein the formation of the sol, the sol-gel matrix and the porous monolith is carried out by a sol-gel process.
2. 2. The method according to claim 1, wherein the sol (5) comprises a phase separation, in particular a pore former.
3. 3. The method according to claim 1 or 2, wherein the sol (5) may be formed by stirring a solution comprising sol-gel precursors, preferably comprising pore former and sol-gel precursors, in particular for a period of at least 5 minutes, better at least 10 minutes, even better at least 15 minutes and / or at most 3 hours, better at most 2 hours, and wherein the temperature is in particular controlled at a substantially constant predetermined value, in particular between 0° C. and 90° C., better between 0° C. and 50° C.
4. 4. The method according to any one of claims 1 to 3, wherein the mould or moulds (15) have at least two openings, at least one of the openings of the mould or each mould (15) opening into the sol after filling.
5. 5. A method according to any one of claims 1 to 4, wherein the or at least one mould (15), better each mould, may be a hollow cylinder, in particular a tube open at its two opposite ends, and wherein the or each mould (15) is preferably arranged within the vessel (12) with its longitudinal axis extending vertically within the vessel.
6. 6. The method according to any one of claims 1 to 5, wherein the container (12) contains several moulds (15), and wherein the filling comprises filling a plurality of moulds (15), each mould (15) comprising at least one opening (17) which opens into the sol (5) after filling, and wherein the filling of the container (12) and the mould or moulds (15) is carried out by injecting the sol (5) into the mould or moulds (15) contained in the container (12) or into the container (12) containing the mould or moulds (15) in such a way that after filling the opening (17) is below the level of the sol (5), or wherein the filling of the container (12) and the mould or moulds (15) is carried out by injecting the sol (5) into the container (12) and then immersing the mould or moulds (15) at least partially, preferably gradually, into the sol (5) contained in the container (12), and when the level of the sol has reached said opening, the mould or each mould is filled with sol through one of its openings.
7. 7. The method according to any one of claims 1 to 6, wherein the step of removing the or each mould (15) together with the sol-gel matrix (25) it contains from the container (12) may comprise removing a block (22) of sol-gel matrix containing the mould or moulds (15) from the container (12) and removing the or each mould (15) and the sol-gel matrix (25) it contains from the previously removed block (22).
8. 8. The method according to any one of claims 1 to 7, comprising removing the sol-gel matrix (25) contained in the mould or moulds from the corresponding mould (15), in particular by controlled pressure on said sol-gel matrix (25), for example by direct pressure using a solid smaller in size than the mould, or by pressure of a gas with a controlled flow rate, or by cutting the mould or moulds (15) or by separating the mould or moulds from each other into two parts.
9. 9. The method according to any one of claims 1 to 8, comprising a controlled generation of mesoporosity in the sol-gel matrix (25) in the mould (15) or in the sol-gel matrix (25) removed from the mould (15) so as to form a sol-gel matrix with hierarchical porosity, the controlled generation of mesoporosity being carried out by immersing the sol-gel matrix (25), whether removed from the mould or each mould (15) or not, after removing the mould or each mould (15) from the container and before forming a porous monolith (35) from the sol-gel matrix (25) of the mould or each mould (15), in particular in an aqueous solution for generating mesoporosity comprising an agent for dissolving the sol-gel matrix and / or a precursor of an agent for dissolving the sol-gel matrix.
10. 10. The method of claim 9, wherein the step of forming the porous monolith (35) comprises drying the sol-gel matrix (25), whether or not removed from the mould or moulds, to form a dried sol-gel matrix, and / or heat treating the sol-gel matrix, particularly after drying, whether or not removed from the mould or moulds.
11. 11. The method according to any one of claims 1 to 10, wherein the method excludes the step of removing the sol-gel matrix (25) from the or each mould (15), the mould being a capillary with an internal diameter d of 5 μm to 3 mm, the capillary having an internal surface that has been activated through a previous activation step, and the generation of mesoporosity is preferably carried out by heating the capillary in an aqueous solution comprising, if applicable, a precursor, in particular urea.
12. A method according to any one of claims 1 to 10, wherein the sol-gel matrix (25) is removed from the or each mould (15) and the resulting porous monolith (35) is self-supporting.
13. A self-supporting porous monolith (35), in particular obtainable using the method according to any one of claims 1 to 12, and having a maximum lateral dimension d strictly smaller than 1 mm.
14. 13. An assembly of a mould, in particular a capillary, and a porous monolith (35) filling at least one cross section of the mould, in particular obtained using a method according to any one of claims 1 to 12, the porous monolith (35) having a maximum lateral dimension strictly greater than 200 μm, the porous monolith having been produced in the mould without a step of shrinking, in particular heat-shrinking, the mould on the porous monolith.
15. 15. A method for liquid phase chromatography, separation and / or extraction and / or adsorption of compounds of interest in complex liquid mixtures, filtration of liquids, or catalysis of liquids by passing the liquid through a porous monolith obtainable by the method according to any one of claims 1 to 12 or a porous monolith according to claims 13 or 14.
Citation Information
Patent Citations
Capillary columns
EP1066513A1